Political accountability under moral hazard - Acharya, Avidit; Lipnowski, Elliot; Ramos, João (American journal of political science, 2025)
Viewing the relationship between politicians and voters as a principal–agent interaction afflicted by moral hazard, we examine how political careers are shaped by the incentives that voters provide incumbents to work in the public interest. When moral hazard binds, the optimal way for voters to hold politicians accountable is to provide re‐election incentives that evolve dynamically over their careers in office. Under these incentives, first‐term politicians are among the most electorally vulnerable and the hardest‐working; politician effort rises with electoral vulnerability; electoral security increases following good performance and decreases following bad performance; and both effort and electoral vulnerability tend to decline with tenure. In extensions, we study limited voter commitment, voluntary retirement from politics, and adverse selection.